Pendidikan Karakter Anak melalui Metode Dialog dan Etika - Kulzum, Putri Maja Mulia (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
The family has a leading and strategic role in the formation of a child's personality, basic character or character. Islam places the family as the first and first basic educational institution. So great and the magnitude of the influence of the family in the education of children, so that Rasulullah SAW connected it with the values ​​of faith. Parents have the first and foremost responsibility in the education of their children. Children are seen as a tabula rasa, where parents are responsible for developing them, both in terms of language development, cultural traditions, and moral beliefs and practices. It is parents who play a role in developing good character in the lives of their children later in life. Ethical education, dialogue and assignment to educate children are excellent and effective methods of implementation. Children are a gift from God who will later grow up independent and free from parental supervision, therefore children must be equipped with strong faith and firm rules in carrying out their lives later. In general, parents and educators only make psychology books or parenting books for guidance in educating children. Rarely do they make the Al-Quran and Sunnah as a reference in implementing education. Islam is a religion of rahmatan lil alamin which has specific methods and methods for improving and educating children. The way of educating is of course adapted to the age level and maturity of the child's thinking. The conclusion from the results of the research that the author conducted shows that the concept of educating children with ethics, dialogue and giving assignments from an Islamic education perspective can be relevant not only in the family environment but also in the school and community environment.